Diet of Phylloicus (Trichoptera: Calamoceratidae) caddisfly larvae in forest streams of western Pará, central Brazilian Amazonia - Pimentel,Diego Ramos (2020)
Abstract: Aim The aquatic larvae of the Phylloicus (Trichoptera: Calamoceratidae) caddisflies are typical shredders. However, the trophic classification of Phylloicus has been based on the morphology and behaviour of the larvae. The aim of this study was to investigate the diet of caddisfly larvae Phylloicus in streams. Methods In order to provide a more reliable classification of Phylloicus diet, we analyzed the stomach contents of 185 larvae collected, sampled with D-frame entomological net from 18 streams located in the tropical forests of western Pará, Brazil. We compared the stomach contents between the larval stages, seasons (dry and rainy), and substrates (i.e., sand, leaf litter, roots, clay and mixed substrates). Results We identified the stomach contents as fine particulate organic matter (FPOM), coarse particulate organic matter (CPOM) and plant tissue. The diet of the Phylloicus larvae was composed basically of FPOM, independent of the larval stage (90,4%), was a higher consumption of FPOM in the dry season and there were no significant differences in food resource between substrates. Conclusions These findings indicate that the classification of Phylloicus as a shredder may in fact be based on the processing of leaves for the building of larval cases, rather than the diet, which is in fact detritivorous, enjoying the availability of FPOM in the streams. The great quantity of FPOM consumed by caddisfly larvae Phylloicus highlight the importance of this food resource for macroinvertebrate communities from tropical streams. Therefore, regional studies of feeding habits are needed for accurate classification trophic of Phylloicus.